TEN YEARS AFTER - Robertson, Rocke (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1980)
Was the student unrest of the Sixties a symptom of a political wave moving internationally across Western societies, or was it a sign of serious institutional decay in universities? Was there something wrong at McGill, and has it been put right? As history repeatedly shows, effects have seldom much to do with causes; the peace of today does not signal the resolution of yesterday’s conflicts. Rocke Robertson talks from a frankly personal perspective about his own experiences and reflections as Principal during those years over which that wave, as he sees it, splashed and splashed again on our particular beach for a surprisingly lengthy span of time and to the considerable discomfort of the residents. He feels that the movement had salutory though temporary effects on the institutions attacked, and that much of the discontent was unfounded and wasteful of energies and emotions. He admits that the students had one legitimate grievance - in the quality of teaching.